Dimensioning UX Models for Design and Evaluation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper attemptsto find out the available dimensions of user experience models in extant literature. The study observed that there are numeroususer experience models with a number of dimensions. This notwithstanding, there appears to be no concordamong practitioners and researchers on the dimensioning of UX models. The reason for lack of consensus is due tounderlying nature of user experience which signifies that UX should be structured and dimensioned differently dependent on the context and domain of use. Seemingly every experience is particularly unique and is situated in time and context, thus making the dimensioning of UX to vary and differ. A close look at prior literature indicate that several user experience models exist but their dimensions are however not comprehensive enough for a holistic design and evaluation of digital applications experiences. To this end, this study proposed a set of dimensions for interactive systems that will aid a more comprehensive and holistic design and evaluation of the user experience of interactive applications.